Effect of platelet-shaped graphene additives on actuating response of carbon nanotube/ionic liquid/polymer composite actuators. (23rd January 2018) - Monobe, Hirosato; Tsuchiya, Nobuyuki; Yamamura, Masahiro; Mukai, Ken; Sugino, Takushi; Asaka, Kinji
Abstract: In this study, the platelet-shaped graphene was used as a conductive additive in porous electrodes of a dry-type polymer actuator consisting of carbon nanotube (CNT), ionic liquid, and a base polymer to improve actuation properties. The generated strain was estimated from the bending motion of the actuator in the frequency range from 0.005 to 10 Hz. Ten different types of electrode film were prepared by changing the mixing amounts and surface areas of the platelet-shaped graphene. When a small amount of graphene (30 mg) relative to CNT (50 mg) was added to the CNT electrode, the strain was increased to be almost twice larger than that of CNT (50 mg) without any additives. The strain coefficient of the three-layered actuator with CNT electrodes with graphene additives is positively correlated with the capacitance per volume of such electrodes.